Developing a simulation game to facilitate acquisition of knowledge on road safety for schoolchildren - M Ariffin, Mazeyanti; Haron, Nazleeni Samiha; Abd Aziz, Irzan Ashraf (2010)
Due to rising number of traffic accidents in Malaysia, road safety program was introduced in schools as a prevention and reduction steps to educate schoolchildren on the road safety.However, the current methods used for transferring road safety knowledge are not effective since they do not stimulate and motivate children to learn and acquire the right knowledge.Therefore, we propose a simulation game called Road Train Safety Game as an alternative method to transfer road safety knowledge for children aged from 7 to 12 years old.In this paper, we report on the development of the simulation game and discuss on features of the games that promote motivating knowledge acquisition for the children.